PENGARUH MEDIA ORGANIK SEBAGAI MEDIA SAPIH TERHADAP KUALITAS BIBIT BIDARA LAUT (Strychnos lucida R. Brown) - Anita Apriliani Dwi Rahayu; Resti Wahyuni (Jurnal Pemuliaan Tanaman Hutan, 2016)
Timber utilization of Strychnos lucida R. Brown as a medicine caused uncontrolled exploitation. Currently unknown nursery technique appropriate to Strychnos lucida. The aim of this research wastesting the organic media such as eceng gondok compost, rice skin ash and cocopeat as growing media so was produced the best quality of Strychnos lucida seedling. The research used Randomized Complete Block Design with four treatments: B0 (top soil + organic compost (1:1)), B1 (eceng gondok compost + rice husk ash + cocopeat (2:2:1)), B2 (eceng gondok compost + rice husk ash + cocopeat (2:1:2)), and B3 (eceng gondok compost + rice husk ash + cocopeat (1:2:2)). The results showed that growing media only significantly influence on the total of leave, while others parameter such as life percentage, height, diameter, root/shoot ratios (R/S), seedling quality index (QI), and seedling sturdiness were not significantly influence. Duncan test showed average of total of leave was significantly different. The best of total of leave obtained in media B0 (7.4 strands).